OBSERVASI PENGELOLAAN TAMAN BUAYA ASAM KUMBANG SELAMA PENDEMI - Ayu Fadhilla; Dewi Nelly Simanjuntak; Dimas Hernowo; Lewi Christo Hutapea (Geography Education Study Program, Universitas Samudra, 2023)
The purpose of this study was to find out the observations on the management of the Asam Kumbang Crocodile Park during a pandemic. The methoObserd used in this study is a qualitative method. The data collection technique used in this study was carried out by observing and documenting the stages of taking pictures directly in the area. The results of this study stated that the condition of the Asam Kumbang Crocodile Park was apprehensive. This can be seen from the lack of visitors to the crocodile captivity due to the low level of cleanliness in the captive area. In addition to the cleanliness of the breeding area, the cleanliness of crocodiles also needs attention. The important things that are done to manage crocodile captivity are crocodile management, cage management, health and the environment.